Cloud Computing: Solusi Untuk Information And Communication Technology - Tobias Duha; Firdaus Laia; Muhammad Kailani Ridwan; Saifudin; Tutik Maryana (Jurnal Informatika, 2022)
Cloud computing is one of the hottest topics that exist today, in the era of the continuous development of information and communication technology. The emergence of cloud computing technology is an effort to access resources and applications from anywhere via the internet, with this being able to overcome the limitations in utilizing the previous ICT infrastructure. Cloud computing is defined as a convenient network access model to unify the configuration of computing resources such as networks, servers, storage media, applications, and services, and can be configured quickly with minimal administrative effort or interactively. The discussion begins with a description of some opinions or points of view from previous studies on cloud computing technology, then reviewing the possible advantages and disadvantages of implementing cloud computing. Then it ends with a conclusion whether cloud computing is an ICT solution and recommendations that users can consider when implementing cloud computing.